The impact of gender on attainment in learning English as a foreign language - Główka, Danuta (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2014)
This study examined the impact of gender on students’ achievement in learning English as a foreign language in secondary and higher vocational schools in Poland, as well as teachers’ and stu-dents’ opinions concerning the importance of this influence. The collected data provided ample evidence that girls achieved significantly better results than boys. Such results support the socio-linguistic finding that female students outperform males as they are more open to new linguistic forms in the target language and eradicate interlanguage forms that deviate from target lan-guage norms more readily than their male counterparts (Ellis, 2012). However, these findings were not reflected in the opinions of the student and teacher participants. Both parties held a strong conviction that gender played no major role in learning English. The article concludes by outlining some implications for educational policy makers and foreign language teachers.
Keywords: gender; attainment; learning English as a foreign language